8h+26=0

Simple and best practice solution for 8h+26=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8h+26=0 equation:


Simplifying
8h + 26 = 0

Reorder the terms:
26 + 8h = 0

Solving
26 + 8h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 8h = 0 + -26

Combine like terms: 26 + -26 = 0
0 + 8h = 0 + -26
8h = 0 + -26

Combine like terms: 0 + -26 = -26
8h = -26

Divide each side by '8'.
h = -3.25

Simplifying
h = -3.25

See similar equations:

| 9x=x^2-8 | | 5/360 | | 6/408 | | x+20=1.25x | | (x-3)(x+5)=x*x-7x-15 | | 3x=5(4+x) | | 5(4x)-1/2x | | (x+2)(x+3)=x*x+5x+6 | | -76=6x+8 | | x-(-7-x)=35 | | 5/215 | | 9/801 | | 4/356 | | 5/340 | | 3000-120w=4000-160w | | 37=12t | | 55=(1/5)(285-10*e) | | 3*x+7=31 | | ln(5x)=2 | | 8/272 | | 3/162 | | -(3+-6)=-24 | | 17x=-8 | | 2/3x=2/7 | | 30+3x=35+1x | | 0.3(x-2)=1.2 | | 6/252 | | 27=3+8u | | 6-n=13 | | -79=-3-4b | | 5-4a=3+2a | | -5c+7-6c=-59 |

Equations solver categories